Effects of oral anticoagulant therapy in patients with pulmonary diseases - Lai, Jiying; Feng, Shenghui; Xu, Shuo; Liu, Xin (Frontiers in Cardiovascular Medicine, 2022)
Background: To evaluate the effect of oral anticoagulants (OACs) therapy, including vitamin K antagonist (VKA) and direct oral anticoagulants (DOAC) in patients with pulmonary diseases. Methods: Literature from PubMed, MEDLINE, and Cochrane Library were screened until June 2022. Studies assessing OACs for pulmonary hypertension (PH), pulmonary embolism (PE), pulmonary fibrosis (PF), or chronic obstructive pulmonary disease (COPD) were evaluated for inclusion. Results: Our study indicated that in patients with PH, PE and COPD, OACs could significantly reduce the mortality risk, and the effects of VKA and DOACs without statistical difference in reducing the risk of recurrent embolism events. In patients with Idiopathic Pulmonary Fibrosis (IPF), vitamin K antagonist (warfarin) significantly increased the mortality risk, while DOACs were not. As for the safety outcome of OACs, existing studies indicate that compared with patients treated with warfarin, the users of DOAC have a lower risk of major bleeding, while there is no statistical significance between them in nonmajor bleeding events. In current guidelines, the anticoagulation regimen for patients with pulmonary disease has not been defined. The results of our study confirm that DOACs (apixaban, rivaroxaban, dabigatran, and edoxaban) are superior to VKAs in the efficacy and safety outcomes of patients with pulmonary disease. Conclusions: OAC therapy brings benefits to patients with PH, PE, and COPD. Compared with VKA, DOAC is a non-inferior option for anticoagulation in pulmonary disease treatment. Further studies are still needed to provide more reliable evidence about the safety outcome of pulmonary disease anticoagulation.